(untitled) (Research, Society and Development, 2020)
Objective: to analyze what the scientific literature points about productions of academic leagues (AL) in health sciences in Brazilian territory; to know the profiles of academic leagues presented in the literature and to describe the impacts generated by the productions of academic leagues, used for the teaching of undergraduates and society. Method: integrative review study, of a quantitative approach, with articles published between the years 2013 to 2019, using the descriptors: Higher Education; Students of Health Sciences and Academic Success and the term “academic league”. The bases used were MEDLINE, LILACS and SCIELO. Results: 10 studies met the inclusion criteria, which were analyzed through the Teaching, Research and Extension axes. In this study, the ALs came mostly from the southeast region, linked to undergraduate courses in medicine and public educational institutions. Expository classes and participation in scientific events were the most frequent strategies in Teaching and Research, health education activities and assistance activities for Extension. As for the impact, the AL brought contributions by making contact with the practical field under supervision, promoting access to health by the population and health education. Conclusion: the AL encompassed several themes and forms of action, with no distribution patterns on such factors. The analyzed axes proved to be widely attended, contributing to a better understanding of the importance of AL developments. The impact could not be strongly assessed due to the absence of such data in primary studies.